2014
DOI: 10.1007/s00228-014-1690-1
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of the UGT1A4 gene polymorphism with serum concentration and therapeutic efficacy of lamotrigine in Han Chinese of Northern China

Abstract: Patients with the UGT1A4 142TT polymorphism had a higher blood LTG concentration and better therapeutic efficacy, suggesting that this polymorphism influences LTG activity. The UGT1A4 127delA polymorphism significantly affected LTG levels and increased one of our patient's susceptibility to LTG-related adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
39
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 22 publications
8
39
0
1
Order By: Relevance
“…Clearly, as the effect of *2 in our study was non-significant, this finding needs to be confirmed by others. With regard to our results on *3, decreases in drug serum concentrations have also been reported by others (Chan 2013;Chang et al 2014;Ghotbi et al 2010;Gulcebi et al 2011). Paradoxically, in the Chan study (2013), significantly lower LTG serum concentrations were found in heterozygous individuals (wild type/ *3), but not in homozygous individuals (*3/*3).…”
Section: Enzyme Inhibitorsupporting
confidence: 78%
See 3 more Smart Citations
“…Clearly, as the effect of *2 in our study was non-significant, this finding needs to be confirmed by others. With regard to our results on *3, decreases in drug serum concentrations have also been reported by others (Chan 2013;Chang et al 2014;Ghotbi et al 2010;Gulcebi et al 2011). Paradoxically, in the Chan study (2013), significantly lower LTG serum concentrations were found in heterozygous individuals (wild type/ *3), but not in homozygous individuals (*3/*3).…”
Section: Enzyme Inhibitorsupporting
confidence: 78%
“…High serum concentrations during treatment initiation with LTG are associated with a higher risk for severe cutaneous reactions and other adverse effects (Chang et al 2014;Guberman et al 1999). On the other hand, low drug serum concentrations may lead to insufficient therapeutic efficacy (Chang et al 2014). Polymorphisms in the coding region of the UGT1A4 gene may alter enzyme activity and thereby lead to reduced or enhanced elimination of LTG and, thus, altered serum concentrations.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Such a variation may lead to significant differences in the hepatic clearance of many AEDs [37], with increase or reduction in metabolic capacity resulting in different phenotypes [38]. Similarly, renal clearance can be affected by differences in the expression level of renal transporters [39,40].…”
Section: Clearance: Influence Of Genotype Size and Maturationmentioning
confidence: 99%